An argument against the axiom of uniform stress being applicable to trees. Issue 3 (2nd July 2016) - Slater, Duncan
Abstract : The axiom of uniform stress is based on the theory that trees carry out their secondary growth in such a way that bending stresses are averaged out over the outer surfaces of the tree and the tree's resulting aerial form avoids stress concentrations and repairs "notch stresses". However, this can be shown, by combining a series of logical propositions, to be an errant or incomplete concept of how tree form develops, even in the limited scope of local stress levels that component parts of trees experience due to gravitational or dynamic wind loading. This paper presents an argument against the veracity of this axiom and highlights the extent of contradictory scientific work on the adaptive responses of trees to strain, their dynamic movement in the wind and the habit of some species to fail in a graduated way. It is concluded that a better model of the biomechanical behaviour of trees can be achieved through a synthesis of existing scientific models.